Survey of identity resolution system in industrial Internet of things - Yuzheng REN; Renchao XIE; Shiqin ZENG; Haoran ZHAO; Jiayi YU; Ru HUO; Tao HUANG; Yunjie LIU (Tongxin xuebao)
With the development of the internet of things (IoT),5G and industrial technology,industrial IoT has become a new research field.Due to the specific requirements of delay,security and stability in industrial production,the traditional DNS has limitations to meet the needs of industrial IoT because of its single identity object,rigid resolution results,and weak security.In this context,how to provide efficient,flexible and secure resolution services for universal objects has become a hot area worldwide.Firstly,we discussed the design principles and key supporting technologies of the identity resolution system in industrial IoT.Then summarized and compared the existing identity resolution systems in detail.Next,the new identity resolution schemes in academic research were introduced.Finally,the core problems and the future research trend in this field were discussed.